Evaluation of the reflective practice programme - Nelumbu, Lucia (International Journal of Medicine, 2015)
It was obvious that the developed programme would be evaluated after the implementation process. The programme was evaluated after four months of implementation on the application of the content of the programme.Â  The researcher organised a focus group discussion for the registered nurses in order to gain information regarding the implementation of the developed programme. The participants were invited on basis of their participation in the previous implementation and training workshop of the reflective practice programme. The participants concluded that this is an effective and fruitful approach for all health providers, which is helping them to identify their mistakes and to reflect on their daily practice in order to make improvements. This approach assists them on how to set priorities and assign tasks to other colleagues to work as a team. Moreover this programme helped the registered nurses to know how to assist the patients even when they did not call for help and also to realize the need to attend to the patientsâ€™ calls immediately. This programme also drew the attention of the registered nurses to the necessity of treating patients as human beings.